Natural history of small asymptomatic kidney and residual stones over a long‐term follow‐up: systematic review over 25 years. (6th September 2021) - Lovegrove, Catherine E.; Geraghty, Robert M.; Yang, Bingyuan; Brain, Eleanor; Howles, Sarah; Turney, Ben; Somani, Bhaskar
Abstract : Objective: To systematically review the natural history of small asymptomatic kidney and residual stones, as the incidental identification of small, asymptomatic renal calculi has risen with increasing use of high‐resolution imaging. Materials and methods: We reviewed the natural history of small asymptomatic kidney and residual stones using the Cochrane and Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) methodology. We searched MEDLINE, Scopus, EMBASE, EBSCO, Cochrane library and Clinicaltrials.gov using themes of 'asymptomatic', 'nephrolithiasis', 'observation', 'symptoms', 'admission', 'intervention' and similar allied terms for all English language articles from 1996 to 2020 (25 years). Inclusion criteria were studies with ≥50 patients, stones ≤10 mm, and a mean follow‐up of ≥24 months. Primary outcomes were occurrence of symptoms, emergency admission, and interventions. Results: Our literature search returned 2247 results of which 10 papers were included in the final review. Risk of symptomatic episodes ranged from 0% to 59.4%. Meta‐analysis did not identify any significant difference in the likelihood of developing symptoms when comparing stones <5 mm to those >5 mm, nor those <10 mm to those >10 mm. Risk of admission varied from 14% to 19% and the risk of intervention from 12% to 35%. Meta‐analysis showed a significantly decreased likelihood of intervention for stones <5 vs >5 mm and <10 vs >10 mm. Studies had variable risk of bias due to heterogeneous reporting of outcome measures with significant likelihood that observed differences in results were compatible with chance alone (Symptoms: I 2 =0%, Cochran's Q = 3.09, P  = 0.69; Intervention: I 2 =0%, Cochran's Q = 1.76, P  = 0.88). Conclusions: The present systematic review indicates that stone size is not a reliable predictor of symptoms; however, risk of intervention is greater for stones >5mm vs <5 mm and >10 vs <10 mm. This review will inform urologists as they discuss management strategies with patients who have asymptomatic renal stones and offer insight to committees during the development of evidence‐based guidelines.